Surfactant and a mixture of surfactant and nanoparticles to stabilize CO2/brine foam, control gas mobility, and enhance oil recovery - Zuhair A. Al Yousef; Mohammed A. Almobarky; David S. Schechter (Journal of Petroleum Exploration and Production Technology, 2019)
Abstract Injecting carbon dioxide into oil reservoirs has the potential to serve as an enhanced oil recovery (EOR) technique, mitigating climate change by storing CO2 underground. Despite the successful achievements reported of CO2 to enhance oil recovery, mobility control is one of the major challenges faced by CO2 injection projects. The objective of this work is to investigate the potential of using surfactant and a mixture of surfactant and nanoparticles to generate foam to reduce gas mobility and enhance oil recovery. A newly developed anionic surfactant and a mixture of the surfactant and surface-modified silica nanoparticles were used to assess the ability of generating a stable foam at harsh reservoir conditions: sc-CO2 and high temperature. Dynamic foam tests and coreflood experiments were conducted to evaluate foam stability and strength. To measure the mobility of injected fluids in sandstone rocks, the foam was generated by co-injection of sc-CO2 and surfactant, as well as a mixture of surfactant and nanoparticles at 90% quality. The coreflood experiments were conducted using non-fractured and fractured sandstone cores at 1550 psi and 50 °C. The use of surfactant and mixture was able to generate foam in porous media and reduce the CO2 mobility. The mobility reduction factor (MRF) for both cases was about 3.5 times higher than that of injecting CO2 and brine at the same conditions. The coreflood experiments in non-fractured sandstone rocks showed that both surfactant and a mixture of surfactant and nanoparticles were able to enhance oil recovery. The baseline experiment in the absence of surfactant resulted in a total recovery of 71.50% of the original oil in place. However, the use of surfactant was able to bring oil recovery to 76% of the OOIP. The addition of nanoparticles to surfactant, though, resulted in higher oil recovery, 80% of the OOIP. In fractured rocks, oil recoveries during secondary production mechanisms for the mixture, the surfactant alone, and sc-CO2 alone were 12.62, 8.41, and 7.21% of the OOIP, respectively. Huge amount of oil remains underground following the primary and secondary oil production schemes. CO2 has been widely used to enhance oil recovery. However, its high mobility might result in unfavorable and unsuccessful projects. The use of specially designed surfactants and the synergistic effect of surfactant and nanoparticles may provide a solution to stabilize CO2/brine foam at harsh reservoir conditions and, therefore, reduce the gas mobility and, consequently, enhance oil recovery.